With letters of light : studies in the Dead Sea scrolls, early Jewish apocalypticism, magic and mysticism in honor of Rachel Elior - Orlov, Andrei A., 1960-; Arbel, Daphna (Ekstasis (Walter de Gruyter & Co.), 2011)
This collection of essays is a tribute to Rachel Elior's decades of teaching, scholarship and mentoring. If a Festschrift reflects the individuality of the honoree, then this volume offers insights into the scope of Rachel Elior's interests and scholarly achievements in the study of the Dead Sea Scrolls, Jewish apocalypticism, magic, and mysticism from the Second Temple period to the later rabbinic and Hekhalot developments. The majority of articles included in the volume deal with Jewish and Christian apocalyptic and mystical texts constituting the core of experiential dimension of these reli.